Do children with cystic fibrosis receiving outreach care have poorer clinical outcomes than those treated at a specialist cystic fibrosis centre?. (17th November 2016) - Weber, Heinrich C.; Robinson, Philip F.; Saxby, Nicole; Beggs, Sean A.; Els, Ingrid; Ehrlich, Rodney I.
Abstract: Introduction: Although cystic fibrosis (CF) centre care is generally considered ideal, children living in regional Australia receive outreach care supported by the academic CF centres. Methods: This is a retrospective database review of children with CF treated at the Royal Children's Hospital in Melbourne and its outreach clinics in Albury (Victoria), and Tasmania. The aim was to compare the outcomes of children with CF managed at an academic centre with that of outreach care, using lung function, nutritional status and Pseudomonas aeruginosa colonisation. Three models of care, namely CF centre care, Shared care and predominantly Local care, were compared, based on the level of involvement of CF centre multidisciplinary team. In our analyses, we controlled for potential confounders, such as socio‐economic status and the degree of remoteness, to determine its effect on the outcome measures. Results: There was no difference in lung function, i.e. forced expiratory volume in 1 s (FEV1 ), the prevalence of Pseudomonas aeruginosa colonisation or nutritional status (body mass index (BMI)) between those receiving CF centre care and various modes of outreach care. Neither socio‐economic status, measured by the Socio‐Economic Index for Area (SEIFA) for disadvantage, nor distance from an urban centre (Australian Standard for Geographical Classification (ASGC)) were associated with lung function and nutritional outcome measures. There was however an association between increased Pseudomonas aeruginosa colonisation and poorer socio‐economic status. Conclusion: Outcomes in children with CF in regional and remote areas receiving outreach care supported by an academic CF centre were no different from children receiving CF centre care.